Determining the relationship between obesity and its comorbidities among adult diabetic patients attending the general outpatient clinic at a tertiary health institution in South-Eastern Nigeria - Onyechere, Jennifer C.; Uwaka, Obiajulu E.; Uzoma, Ifunanya G.; Mbatuegwu, Chidi U.; Ewurum, Odochi; Ogor, Kingsley I.; Aisuodionoe, Michael E. (International Journal Of Community Medicine And Public Health, 2025)
Background: Today, more than 1.1 billion adults worldwide are overweight and 312 million of them are obese. This growing prevalence of overweight and obesity had led to a propelling upsurge in cases of diabetes especially type 2. However, diabetes is a major predisposing factor of cardiovascular diseases which accounts for about 18 million death every year. This study was aimed at determining the relationship between obesity and its comorbidities among adult diabetic patients attending the GOPC at a tertiary health institution in Nigeria. Methods: This was a cross-sectional, descriptive, and hospital-based study carried out at Federal Medical Centre, Owerri, within a four months period. Data was collected using a structured interviewer administered questionnaire and was analyzed using social package for the social sciences (SPSS) version 17 computer software, with all p values considered significant at values <0.05. Results: A total of 216 diabetics (subjects) and 216 age, and sex matched non-diabetics (control) were studied over a period of four months. In both the study and control group their mean age was 54.70±10.59 years with females accounting for 66.9% (123) and males 43.1% (93) resulting to a male; female ratio of 1:1.3. Ninety-four (43.5%) of the diabetics were overweight, 70 (32.4%) were obese while 52 (24.1%) had normal weight. There was a statistically significant relationship between type 2 diabetes mellitus and body mass index (BMI) (p=0.000) wherein diabetics subjects tend to have higher than normal BMI. Conclusion: This study demonstrated a significant association between type 2 diabetes mellitus (DM), BMI, physical inactivity and hypertension while dyslipidaemia did not.